The Diffusion of Technological Progress in ICT - Steffen Elstner; Christian Grimme; Valentin Kecht; Robert Lehmann (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study whether technology gains in sectors related to Information and Communications Technology (ICT) increase productivity in the rest of the economy. To separate exogenous gains in ICT from other technological progress, we use the relative price of ICT goods and services in a structural VAR with medium-run restrictions. Using local projections to estimate the effect of ICT-related technology gains on sectoral technology (TFP), we find two sets of results. First, since the mid-2000s there have been positive and persistent technology spillovers to sectors intensively using ICT. Second, neglecting leasing activity leads to an overestimation of the TFP response for all sectors except the leasing sector, where it is strongly underestimated.
Keywords: C32; D24; E22; E24; O33; O47; O52; 330; digitization; information and communications technology; technology shocks; local projections; structural VARs; medium-run restrictions; growth accounting